The RhoGEF domain of p210 Bcr-Abl activates RhoA and is required for transformation - Sahay, S; Pannucci, N L; Mahon, G M; Rodriguez, P L; Megjugorac, N J; Kostenko, E V; Ozer, H L; Whitehead, I P (Oncogene, 2008)
The BCR-ABL oncogene encodes an in-frame fusion protein containing N-terminal sequences derived from Bcr and C-terminal sequences derived from Abl. Bcr contains a centrally located Rho-specific guanine nucleotide exchange factor (RhoGEF) domain that is retained within p210 Bcr-Abl. Although this domain is subject to autoinhibition in the context of Bcr, here we show that it is constitutively activated in p210 Bcr-Abl. p210 Bcr-Abl can stimulate RhoA activation independently of its tyrosine kinase activity, and mutations within the RhoGEF domain that are predicted to eliminate RhoGEF activity inhibit RhoA activation. The RhoGEF mutant of p210 Bcr-Abl does not affect the tyrosine kinase activity of the molecule, nor the ability of p210 Bcr-Abl to interact with XPB through the RhoGEF domain. Despite retaining normal levels of tyrosine kinase activity, the RhoGEF mutant of p210 Bcr-Abl is impaired in transforming activity as measured by anchorage-independent growth. However, the mutant is still able to confer the phenotype of growth factor independence in myeloid cells, suggesting that some, but not all parameters of p210 Bcr-Abl transformation, are dependent upon a catalytically active RhoGEF domain. Collectively, these observations identify a gain-of-function activity attributable to the RhoGEF domain of p210 Bcr-Abl that is required to support the transformed phenotype.